Emerging Adult Report of Childhood Maltreatment and Related Facets of Impulsivity - Rogers, Mary Moussa (Journal of interpersonal violence, 2022)
Childhood maltreatment is related to a host of outcomes, many of which may be partially explained by the transdiagnostic factor of impulsivity. The research linking maltreatment to impulsivity is well supported. However, research differentiating between emotional and physical maltreatment and impulsivity is lacking, particularly with regard to facets of trait impulsivity. Thus, the current study examined the links between childhood emotional and physical maltreatment and current impulsivity traits of positive and negative urgency, lack of perseverance, lack of premeditation, and sensation seeking in emerging adults. Furthermore, effects of maltreatment are known to differ by the gender of the parent and the gender of the child. Thus, differences between parent-emerging adult child gender dyads were also examined. Results suggested both physical and emotional maltreatment were associated with negative urgency across the parent?child gender dyads. Emotional maltreatment and physical maltreatment differed in relation to impulsivity facet across parent and child gender. Results contribute to a knowledge base to use in future exploration of emotional and physical maltreatment outcomes and targets of intervention.